TRUE PROLAPSE OF GRAVID UTERUS, BLADDER AND INTESTINES THROUGH VAGINAL TEAR IN A G - PRAVEEN, S; JAYAKUMAR, C; ARAVIND, AMRITHA; ABHILASH, R S (The Indian Journal of Animal Reproduction, 2016)
A rare condition of prolapse of gravid uterine horns along with partially filled bladder and intestines through a tear in the vaginal floor in a crossbred malabari doe was prsented. Hysterotomy was performed and two immature live fetuses were extracted out, following which the uterus was sutured and repositioned through the vaginal tear that was then repaired.